Sell-side analysts with accounting experience - Andres, Christian; Brochet, Francois; Limbach, Peter; Schumacher, Nicola (Review of Accounting Studies, 2026)
This study documents the performance and career outcomes of sell-side analysts with prior accounting education or experience. Analysts with accounting work experience—especially former auditors—issue more accurate earnings forecasts and more profitable sell recommendations. In contrast, analysts with only accounting education or CPA credentials do not outperform. Former auditors also ask more accounting-focused questions during earnings calls, and the firms they cover exhibit higher earnings quality and more conservative reporting, consistent with improved monitoring. In terms of labor market outcomes, these analysts have longer tenures, are marginally more likely to attain all-star recognition, and are more often assigned to firms with complex financial reporting and greater analyst competition, suggesting strategic deployment. Overall, our findings highlight the value—but also the limits—of accounting expertise in sell-side research, particularly as it relates to information processing, capital market intermediation, and professional advancement.